Psychometric characteristics of the reference-narrator test in educational research according to the paragraph response theory (Journal of the College of Basic Education, 2022)
This study aimed to use the paragraph response theory in constructing a verbal reference test in educational research according to the one-teacher logistic model. A test was prepared to measure student achievement in the educational research course, consisting of (48) items of the type of choice from four alternatives. From the test items of the model's expectations, (4) items that did not conform to the model were deleted, and the results showed that the teachers' estimates of difficulty and discrimination are among the accepted criteria in the educational and psychological measurement literature.